The murder list [large type] - Ryan, Hank Phillippi (Thorndike Press large print mystery, 2019)
"Law student Rachel North will tell you, without hesitation, what she knows to be true. She's smart, she's a hard worker, she does the right thing, she's successfully married to a faithful and devoted husband, a lion of Boston's defense bar, and her internship with the Boston DA's office is her ticket to a successful future. Problem is--she's wrong. And in this cat and mouse game--the battle for justice becomes a battle for survival. The Murder List is a new standalone suspense novel in the tradition of Lisa Scottoline and B. A. Paris from award-winning author and reporter Hank Phillippi Ryan"--